In Vivo Two-Photon Ca(2+) Imaging Reveals Selective Reward Effects on Stimulus-Specific Assemblies in Mouse Visual Cortex - Goltstein, Pieter M. (J Neurosci, 2013)
Experiences can alter functional properties of neurons in primary sensory neocortex but it is poorly understood how stimulus–reward associations contribute to these changes. Using in vivo two-photon calcium imaging in mouse primary visual cortex (V1), we show that association of a directional visual stimulus with reward results in broadened orientation tuning and sharpened direction tuning in a stimulus-selective subpopulation of V1 neurons. Neurons with preferred orientations similar, but not identical to, the CS+ selectively increased their tuning curve bandwidth and thereby exhibited an increased response amplitude at the CS+ orientation. The increase in response amplitude was observed for a small range of orientations around the CS+ orientation. A nonuniform spatial distribution of reward effects across the cortical surface was observed, as the spatial distance between pairs of CS+ tuned neurons was reduced compared with pairs of CS− tuned neurons and pairs of control directions or orientations. These data show that, in primary visual cortex, formation of a stimulus–reward association results in selective alterations in stimulus-specific assemblies rather than population-wide effects.